Tinjauan Fikih Muamalah Terhadap Sistem Kerjasama Mudharabah antara Pemilik Armada (Dump Truck) dengan Sopir (Studi Kasus PT X Gresik, Jawa Timur) - Hendra Kholid; Sirly Tsania Auladah (Al-Mizan : Jurnal Hukum dan Ekonomi Islam, 2023)
In Gresik, there is a quarrying transaction, namely the excavation of limestone by PT. X where providing limestone delivery services takes place between the fleet owner (dump truck) and the driver both of whom work together, in practice using a mudhᾱrabah contract. Therefore the owner of the fleet (Dump Truck) as shahibul maal who has given 100% of the funds to the driver as manager (mudharib) has been mutually agreed upon at the beginning of profit sharing or profits in working together in a transparent manner. If there is a loss, shahibul mal is the one who bears the loss. The research method used is field research with a qualitative type. The author collects data from interviews, observation and literature review. Then the researcher grouped the data and then analyzed it based on the theoretical basis. The results of the study concluded that: first, the practice of cooperation using a mudharabah contract is in accordance with the pillars and conditions that are carried out, so that it can be said to be in a valid mudhᾱrabah. Second, the profit-sharing system used by fleet owners (dump trucks) and drivers with an agreement of 85%: 15% is in accordance with the initial agreement, but in terms of profit-sharing it is felt to be less open (transparency) from shahibul mal to mudharib. This is because the jurisprudence of the Imam Syafi’i school prioritizes the side of openness and transparency in managing both the amount of capital or in profit sharing and so on.